The Influence of Regional Financial Independence on Regional Financial Conditions - Dila Dasma (Value Relevance: Jurnal Akuntansi, 2024)
This study aims to determine the effect of regional financial independence on the financial condition of the Papua Provincial Government for the 2019-2023 period. This type of research is quantitative research with descriptive analysis methods. The sample was taken using a purposive sampling technique. The sample amounted to 30, with the population used in this study being 1 (one) City and 5 (five) Regencies in Papua Province. The data analysis technique used was the Panel Data Regression analysis using SPSS. The results of this study show that regional financial independence has a positive and significant influence on the financial condition of the Papua Province region for the period 2019-2023. This indicates that the more financially independent an area is, the better its financial condition will be.